Human Resource Management Strategies on The Effectiveness Of Zakat Collection and Distribution Lazismu Sidoarjo - Karunia, Dwi; Makhtum, Ahmad (JURNAL EKONOMI SYARIAH, 2023)
Introduction to The Problem: Management of Human Resources (MSDI) plays a very important role in ensuring the effectiveness and sustainability of zakat programsPurpose/Objective Study: This research aims to analyze Human Resource Management Strategies in zakat management at Lazismu Sidoarjo.Design/Methodology/Approach: using both qualitative and quantitative methods, along with field research.Findings: The findings of the IFAS analysis indicate that Lazismu Sidoarjo possesses several significant strengths, especially in terms of legitimate legal status and accreditation by the Ministry of Religious Affairs. However, the research also identifies a primary weakness, which is the limitation in Human Resources (HR), still posing a constraint on the effectiveness of zakat management. Furthermore, the EFAS analysis highlights various opportunities that Lazismu Sidoarjo can leverage, including the certification of zakat administrators recognized at national and international levels, as well as technological advancements supporting zakat operations. On the flip side, there are threats that need vigilance, especially in the context of economic crises such as those encountered during the COVID-19 pandemic. The SWOT analysis places Lazismu Sidoarjo in Quadrant 1 (SO), indicating its position as an organization with robust legality and readiness to adapt to environmental changes by utilizing zakat administrator certification and technology. Therefore, the recommended strategy is to capitalize on existing strengths to address weaknesses while harnessing opportunities and confronting threats through a growth-oriented and innovative approach in zakat management.Paper Type: Research Article